Decentralising authoritarianism? The international intervention, the new 'revolutionaries' and the involution of Post-Qadhafi Libya. (2nd January 2016) - Toaldo, Mattia
Abstract: In 2011, Libya became the only country of the Arab Uprisings where NATO and the Arab League intervened militarily, ostensibly to protect the civilian population, but in reality in support of the opposition National Transitional Council. This article argues that, since 2011, Libya has transitioned from Qadhafi's centralised authoritarianism to a new decentralised authoritarianism where multiple centres of power coexist and sometimes overlap, while leaving room only for formal democratic institutions. This is the result of decisions taken by the 'revolutionaries' after the overthrow of the dictator, and a consequence of long-standing features of the Libyan state and society.